Digital eye strain syndrome among higher education health sciences students in Saudi Arabia: severity and preventive ergonomic practices - Olfat Abdulgafoor Gushgari; Samiha Hamdi Sayed; Wafaa Taha Elgzar (PeerJ)
Background The increased utilization of digital screens is an unavoidable consequence of the technology era. Digital eye strain (DES) is a prevalent health problem among higher education students in Saudi Arabia, especially health sciences students due to the frequent use of digital sources and virtual classes. Thus, this study aimed to assess the severity of digital eye strain syndrome (DESS) symptoms and preventive ergonomic practices among higher education health science students in Saudi Arabia. Methods A cross-sectional study using multistage cluster sampling in three cities (Dammam, Riyadh, Jeddah) in Saudi Arabia. A convenient sample of 328 health science students was selected using an equal allocation technique. The researchers designed and used an online survey of three sections: personal and digital device use-related data, the DESS questionnaire, and the self-reported preventive ergonomic practices scale. Results DESS is a widespread problem among 72.0% of health science students, and 58.2% had unsatisfactory ergonomics. The frequently reported symptoms were blurred vision (32.9%) and increased sensitivity to light (33.5%). The severe eye-related symptoms were headache (45.85%), foreign body inside the eye (43.71%), eye burning (40.19%), and dryness (39.76%). Logistic regression analysis revealed that the female sex, years of screen utilization and the number of hours per day, screen use without rest, and frequency of virtual classes per week, eye disease, digital screen utilization for studying, nonuse of protective eye measures, and using numerous digital devices were significant predictors of DESS risk (P < 0.05). Conclusions DESS is a common problem among many health science students, with headaches and foreign body sensations in the eye being the most frequent symptoms. Screen utilization time and eye disease are significant predictors of DESS, while most items’ application of ergonomic practices was low. Educational programs are needed to increase student’s awareness of ergonomic practices.